Synergy of Islamic Values and Nature School in Building Students' Spiritual-Ecological Character - Abdul Latief Anis; Naufal Ahmad Rijalul Alam (Universitas Muhammadiyah Mataram, 2026)
This research is motivated by the importance of integrating spiritual education and ecological concern in building students' character in the midst of the challenges of moral degradation and environmental crises. Many educational institutions still focus on academic achievement so that the formation of spiritual-ecological character has not been optimally developed. Therefore, this study aims to analyze the synergy of Islamic values and the concept of nature schools in building the spiritual-ecological based character of students in Sayogya (Yogyakarta Nature School). This study uses a qualitative approach with a case study design. The research subjects consisted of five people, namely one school principal or foundation head and four teachers who were selected through purposive sampling. The data collection technique was carried out through in-depth interviews and documentation, then analyzed using qualitative data analysis through data reduction, data presentation, and conclusions drawn. The results of the study show that Sayogya integrates Islamic values through the habituation of faith, morals, worship, and ukhuwah in students' daily activities. The concept of nature schools is applied through real-life experience-based learning such as gardening, animal husbandry, nature conservation, and social interaction with the surrounding community. The synergy between Islamic values and nature-based learning forms the spiritual-ecological character of students which is characterized by the growth of gratitude, responsibility as a caliph on earth, concern for the environment, and simple living behavior. These findings show that the integration of Islamic education and the concept of natural schools can be an effective holistic educational model in shaping a religious, moral, and ecological conscious generation in responding to current educational challenges.